Rising titans, falling giants : how great powers exploit power shifts - Shifrinson, Joshua R. Itzkowitz (Cornell studies in security affairs., 2018)
"Explores the strategies that rising powers adopt toward declining powers and asks why newly powerful states often choose not to take immediate advantage of a former power's weaknesses but rather support and manage that decline in a peaceable fashion"--Provided by publisher.